Correlation Between Anterior Corneal Elevation Differences in Main Meridians and Corneal Astigmatism. Issue 2 (March 2020) - Batres, Laura; Piñero, David; Carracedo, Gonzalo
Abstract : Purpose: To assess the correlation between anterior corneal elevation (ACE) and anterior corneal astigmatism (ACA) obtained with two different topographers in healthy subjects at different corneal diameters. Methods: A retrospective, comparative, and observational study was conducted. Topography data from 305 patients obtained with the Oculus Pentacam (Oculus, Wetzlar, Germany) and Sirius (CSO, Florence, Italy) systems were collected. Subjects were divided into four groups depending on the magnitude of ACA. The ACE was evaluated in the principal meridians at 2, 3, and 4 mm from the corneal apex. The difference in ACE between meridians (ACE-M) and in superior–inferior and nasal–temporal semimeridians (ACE-SM) was calculated. Results: A strong positive correlation between ACE-M and ACA with both topographers was found for all corneal diameters ( P <0.001). A linear equation to calculate the ACE-M differences as a function of the astigmatism at 8 mm of diameter was obtained: y=23.417x+1.40, where y is ACE-M in microns and x is ACA in diopters. Significant differences in ACE along SM were found for all groups studied according to the magnitude of ACA for the horizontal SM ( P >0.001). The temporal meridian was more elevated at 4- and 6-mm diameters, and the nasal semimeridian was the most elevated for 8 mm. Conclusion: Anterior corneal astigmatism and elevation differences are strongly correlated, providing more corneal topography knowledge that could be applied in the contact lens fitting. A toric orthokeratology lens may be indicated in ACA greater than 0.75 D.